2022
DOI: 10.1162/jocn_a_01814
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Memory Precision and Reality Monitoring Following Stimulation of Angular Gyrus

Abstract: The qualities of remembered experiences are often used to inform “reality monitoring” judgments, our ability to distinguish real and imagined events [Johnson, M. K., & Raye, C. L. Reality monitoring. Psychological Review, 88, 67–85, 1981]. Previous experiments have tended to investigate only whether reality monitoring decisions are accurate or not, providing little insight into the extent to which reality monitoring may be affected by qualities of the underlying mnemonic representations. We used a continuo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…TMS over the left AG showed a critical involvement of the left AG in left-right discrimination (Hirnstein et al, 2011). Stimulation of the AG selectively reduced the association between memory precision and self-referential reality monitoring decisions, suggesting a causal role in filling remembered experiences with a sense of self-agency (Kwon et al, 2022). In this domain, many studies showed a particular role of the inferior parietal lobule, including the AG, in the definition of the boundaries of our bodies and in the integration and comparison of sensorimotor information flows to correctly attribute movements agency (for review see (Crivelli and Balconi, 2017)).…”
Section: Agency and Self-processingmentioning
confidence: 90%
“…TMS over the left AG showed a critical involvement of the left AG in left-right discrimination (Hirnstein et al, 2011). Stimulation of the AG selectively reduced the association between memory precision and self-referential reality monitoring decisions, suggesting a causal role in filling remembered experiences with a sense of self-agency (Kwon et al, 2022). In this domain, many studies showed a particular role of the inferior parietal lobule, including the AG, in the definition of the boundaries of our bodies and in the integration and comparison of sensorimotor information flows to correctly attribute movements agency (for review see (Crivelli and Balconi, 2017)).…”
Section: Agency and Self-processingmentioning
confidence: 90%
“…tending to take real events to have been imagined), whereas older children and adults tend to externalize episodic simulations (i.e. falsely take their imaginations to represent past experiences; Kwon et al, 2021).…”
Section: Developmentmentioning
confidence: 99%
“…Such developmental differences in reality-monitoring performance were partly explained by the fact that younger children were unable to appropriately interpret the phenomenal qualities of their episodic representations. In fact, younger children showed an internalization bias (i.e., tending to take real events to have been imagined), whereas older children and adults tend to externalize episodic simulations (i.e., falsely take their imaginations to represent past experiences; Kwon et al, 2022).…”
Section: Evidence Of Cultural Learningmentioning
confidence: 99%
“…Accordingly, the angular gyrus has been implicated in a myriad of cognitive functions, including mental arithmetic, visuospatial processing, inhibitory control, and theory-of-mind (Cattaneo et al, 2009 ;Grabner et al, 2009 ;Lewis et al, 2019 ;Schurz et al, 2014 ). Moreover, there is accumulating evidence pointing to a key role of the angular gyrus in long-term memory (Bellana et al, 2017 ;Bonnici et al, 2018 ;Kwon et al, 2022 ;Wang et al, 2014 ) and imagination (Ramanan et al, 2018 ;Thakral et al, 2017Thakral et al, , 2020. How these putative functions of the angular gyrus relate to one another, however, remained unclear.…”
Section: Introductionmentioning
confidence: 99%